2015
DOI: 10.1021/acs.energyfuels.5b00670
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Heavy Oil Properties under In-Situ Combustion: A Field Study

Abstract: A pilot test of in-situ combustion (ISC) was carried out in Jiang oil field, Junggar basin, China, and a favorable result was obtained. In this work, we systematically studied the changes of crude oil properties during the combustion process. Crude oils were characterized by means of rheology test, SARA (saturates, aromatics, resins, and asphaltenes) fractionation and analyses, CHNO elemental analyses, and acid number (AN) measurements. Furthermore, analyses of FTIR and GC-MS on the resins were carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…In recent decades, heavy oil has become an increasingly significant energy resource because of a declining oil production of conventional oil reserves as well as the rapid rise of global energy demand. , Thermal recovery techniques, involving in situ combustion (ISC), supercritical water, steam injection, binary mixtures, and so forth, turn out to be extremely promising in terms of the exploitation of (extra) heavy crude oils. ISC is now regarded as the most profitable oil recovery process compared to other thermal recovery methods, which was reported to be roughly two to four times more energy-efficient than the steam drive . However, ISC is a notably complicated process including multiphase flow, mass transfer, heat transfer, and a set of chemical reactions in the reservoir, which allows for combining the advantages of steam injection, flue gas flooding, and hot water injection to attain a quite high oil recovery factor. , Nevertheless, approximately 80% of the ISC projects were economic and technological failures, predominantly because of a poor understanding of thermal behavior and kinetics of heavy oils …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, heavy oil has become an increasingly significant energy resource because of a declining oil production of conventional oil reserves as well as the rapid rise of global energy demand. , Thermal recovery techniques, involving in situ combustion (ISC), supercritical water, steam injection, binary mixtures, and so forth, turn out to be extremely promising in terms of the exploitation of (extra) heavy crude oils. ISC is now regarded as the most profitable oil recovery process compared to other thermal recovery methods, which was reported to be roughly two to four times more energy-efficient than the steam drive . However, ISC is a notably complicated process including multiphase flow, mass transfer, heat transfer, and a set of chemical reactions in the reservoir, which allows for combining the advantages of steam injection, flue gas flooding, and hot water injection to attain a quite high oil recovery factor. , Nevertheless, approximately 80% of the ISC projects were economic and technological failures, predominantly because of a poor understanding of thermal behavior and kinetics of heavy oils …”
Section: Introductionmentioning
confidence: 99%
“…ISC is now regarded as the most profitable oil recovery process compared to other thermal recovery methods, which was reported to be roughly two to four times more energy-efficient than the steam drive. 3 However, ISC is a notably complicated process including multiphase flow, mass transfer, heat transfer, and a set of chemical reactions in the reservoir, which allows for combining the advantages of steam injection, flue gas flooding, and hot water injection to attain a quite high oil recovery factor. 4,5 Nevertheless, approximately 80% of the ISC projects were economic and technological failures, predominantly because of a poor understanding of thermal behavior and kinetics of heavy oils.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy oils are characterized by their high viscosity and extremely complex composition, which set up a challenge for oil recovery, transportation, and refining/upgrading processes . In situ combustion (ISC) has been gaining attention worldwide as a promising thermal enhanced oil recovery (EOR) methodology, because is thermally efficient. ISC not only increases the recovery factor, but also has the potential of upgrading the oil, thereby increasing its value. , During ISC, increases in temperature, and the injection of external gases into the reservoir, prompt chemical and physical variations on the different constituents of the system (water, reservoir rock minerals, and organic matter). , Under these conditions, the susceptibility of heavy oils to form stable emulsions may be extremely heightened. Therefore, with the purpose of making this EOR methodology feasible, it is mandatory to understand the compositional changes along ISC and their implications on emulsion stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2015) reported an upgraded oil production from an in situ combustion pilot in Jiang oil field, Junggar Basin, China. A significant oil upgrade was observed, which depends on saturates, aromatics, resins, and asphaltenes (SARA) composition . One important modification on well configurations is using a horizontal production well to produce oil, which is upgraded by a combustion process, which is called toe-to-heel air injection (THAI).…”
Section: Css Follow-up Processes and Simulationmentioning
confidence: 99%